IMPLEMENTASI PENEGAKAN HUKUM TERHADAP ANAK SEBAGAI PELAKU KEKERASAN SEKSUAL DI KOTA PEKANBARU - Salsabila, Putri Nanda; Erdianto, Erdianto; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Article 76 E of Law Number 35 of 2014 concerning Amendments to LawNumber 23 of 2002 concerning Child Protection states that the criminal act ofmolesting a child which is punishable by a minimum sentence of 5 (five) years in prisonis a serious crime, but in reality in the Police Pekanbaru City Resort has several casesof fornication that have not been resolved because the police have stopped investigatingthe cases because mediation has been carried out. This type of research is sociologicallegal research, namely an attempt to see the influence of the enactment of positive lawon people's lives.This research is also descriptive in nature, namely the author tries to describelaw as a form of social control related to the establishment and maintenance of socialrules, with a basic view of the law's ability to control human behavior and createconformity in these behaviors.This research aims to find out how law enforcement is carried out by thePekanbaru City Resort Police, especially Women and Child Protection UnitInvestigators, what obstacles are faced in law enforcement and what efforts can bemade to overcome obstacles to law enforcement at the Pekanbaru City Resort Police.The results of this research explain that law enforcement carried out by thePekanbaru City Police, especially the Women and Children Protection UnitInvestigators, has not been optimal in cases of criminal sexual abuse of children. Theobstacles faced by the Police are the lack of quality and quantity of Women andChildren Unit Investigators, lack of cooperation from the victim or the victim's family inproviding information related to the case being processed, and a lack of public legalawareness. The efforts that the author offers in this research are to improve the qualityand quantity of investigators in the women's and children's unit at the Pekanbaru CityPolice Department, increasing public insight regarding the importance of legalawareness in order to create justice, benefit and public welfare.Keywords: Law Enforcement - Crime - Sexual Abuse - Children.